2022
DOI: 10.3390/plants11070848
|View full text |Cite
|
Sign up to set email alerts
|

Origin, Maturity Group and Seed Coat Color Influence Carotenoid and Chlorophyll Concentrations in Soybean Seeds

Abstract: Soybean (Glycine max (L.) Merrill) seeds are abundant in physiologically active metabolites, including carotenoids and chlorophylls, and are used as an affordable source of functional foods that promote and maintain human health. The distribution and variation of soybean seed metabolites are influenced by plant genetic characteristics and environmental factors. Here, we investigated the effects of germplasm origin, genotype, seed coat color and maturity group (MG) on the concentration variation of carotenoid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Seed color is an important quality determinant for consumers' acceptability (Tomaszewska-Gras et al, 2021); therefore, calculations of three parameters describing color were performed. Considerable variability was also observed among the flax genotypes for seed color parameters, as shown by the range of variation for L*, a*, and b* parameters originating from the variation in the amount of seed pigments (García-Fernández et al, 2021;Gebregziabher et al, 2022). Thus, selection for luminosity and chromaticity (a* and b*) values in flax seeds will be effective, meeting the demand of a diverse market niche.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seed color is an important quality determinant for consumers' acceptability (Tomaszewska-Gras et al, 2021); therefore, calculations of three parameters describing color were performed. Considerable variability was also observed among the flax genotypes for seed color parameters, as shown by the range of variation for L*, a*, and b* parameters originating from the variation in the amount of seed pigments (García-Fernández et al, 2021;Gebregziabher et al, 2022). Thus, selection for luminosity and chromaticity (a* and b*) values in flax seeds will be effective, meeting the demand of a diverse market niche.…”
Section: Discussionmentioning
confidence: 99%
“…Geographical distribution of flax genotypes indicated the existence of wide variability for seed color parameters, yield and quality traits, attributed to genetic factors and growing conditions such as humidity, temperature, rainfall, and shorter exposure to sunlight (Sadohara et al, 2021;Gebregziabher et al, 2022). Significant differences among continents for seed color parameters indicated that their grown seeds had different colors.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll, a fat-soluble pigment found in all photosynthetic organisms, mainly includes chlorophyll a (chl a ) and chlorophyll b (chl b ) [ 29 ]. The determination of chl a and chl b of honeysuckle was carried out as described in references with minor modifications [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…As expected, their benefits are closely linked to their chemical structure and quantities. Indeed, several studies already reported that, in most cases, an increment in phenolics enhances biological potential [65,75,79,[172][173][174][175][176][177]. Therefore, it is not surprising that their interest is increasing worldwide, especially in preventing and/or attenuating several diseases, especially those without medical cures, like AR (Figure 3).…”
Section: Pharmacological Properties Of Dietary Polyphenolsmentioning
confidence: 99%